La responsabilidad del Estado en casos de desplazamiento forzado por causas de violencia (2015)
Forced displacement causes of violence became in recent years, one of the main manifestations of the humanitarian crisis we face in Colombia amid various forms of social conflict, particularly the armed conflict. This major problem calls into question the ability of the state, as the main guarantor of individual and collective rights of the inhabitants of the country. So, it's the same society, claiming the construction of alternatives for a decent life, especially for those populations that have been affected by violence directly; but more profoundly, they are calling for peaceful solutions, legislation and public policies to intervene structural causes and manifestations of this humanitarian crisis.